Ultrafast Sodium Imaging of the Axon Initial Segment of Neurons in Mouse Brain Slices. Issue 3 (3rd March 2021) - Blömer, Laila Ananda; Canepari, Marco; Filipis, Luiza
Abstract: Monitoring Na + influx in the axon initial segment (AIS) at high spatial and temporal resolution is fundamental to understanding the generation of an action potential (AP). Here, we present protocols to obtain this measurement, focusing on the AIS of layer 5 (L5) somatosensory cortex pyramidal neurons in mouse brain slices. We first outline how to prepare slices for this application, how to select and patch neurons, and how to optimize the image acquisition. Specifically, we describe the preparation of optimal slices, patching and loading of L5 pyramidal neurons with the Na + indicator ING‐2, and Na + imaging at 100 µs temporal resolution with a pixel resolution of half a micron. Then, we present a data analysis strategy in order to extract information on the kinetics of activated voltage‐gated Na + channels by determining the change in Na + by compensating for bleaching and calculating the time derivative of the resulting fit. In sum, this approach can be widely applied when investigating the function of Na + channels during initiation of an AP and propagation under physiological or pathological conditions in neuronal subtypes. © 2021 Wiley Periodicals LLC. Basic Protocol 1 : Preparation of cortical slices Basic Protocol 2 : Selection, patching, and Na + fluorescence recording of a neuron Support Protocol : Calibrating Na + fluorescence Basic Protocol 3 : Data analysis